The Nocardia cyriacigeorgica GUH-2 genome shows ongoing adaptation of an environmental Actinobacteria to a pathogen’s lifestyle - Zoropogui, Anthony (BioMed Central, 2013)
BACKGROUND: Nocardia cyriacigeorgica is recognized as one of the most prevalent etiological agents of human nocardiosis. Human exposure to these Actinobacteria stems from direct contact with contaminated environmental matrices. The full genome sequence of N. cyriacigeorgica strain GUH-2 was studied to infer major trends in its evolution, including the acquisition of novel genetic elements that could explain its ability to thrive in multiple habitats. RESULTS: N. cyriacigeorgica strain GUH-2 genome size is 6.19 Mb-long, 82.7% of its CDS have homologs in at least another actinobacterial genome, and 74.5% of these are found in N. farcinica. Among N. cyriacigeorgica specific CDS, some are likely implicated in niche specialization such as those involved in denitrification and RuBisCO production, and are found in regions of genomic plasticity (RGP). Overall, 22 RGP were identified in this genome, representing 11.4% of its content. Some of these RGP encode a recombinase and IS elements which are indicative of genomic instability. CDS playing part in virulence were identified in this genome such as those involved in mammalian cell entry or encoding a superoxide dismutase. CDS encoding non ribosomal peptide synthetases (NRPS) and polyketide synthases (PKS) were identified, with some being likely involved in the synthesis of siderophores and toxins. COG analyses showed this genome to have an organization similar to environmental Actinobacteria. CONCLUSION: N. cyriacigeorgica GUH-2 genome shows features suggesting a diversification from an ancestral saprophytic state. GUH-2 ability at acquiring foreign DNA was found significant and to have led to functional changes likely beneficial for its environmental cycle and opportunistic colonization of a human host.